2013
DOI: 10.1163/15685403-00003249
|View full text |Cite
|
Sign up to set email alerts
|

Northern range extensions and biological notes for three decapods in the eastern North Pacific

Abstract: Examination of invertebrate vouchers collected during bottom trawl surveys conducted by the National Oceanic and Atmospheric Administration's National Marine Eisheries Service revealed northern range extensions of three decapod species. Two of these species are caridean shrimps (Lebbeus washingtonianus (M. J. Rathbun, 1902) (Hippolytidae) and Systellaspis braueri paucispinosa Crosnier, 1987 (Oplophoridae)) and represent the first records in Alaska. The hthodid crab Neolithodes diomedeae (J. E. Benedict, 1895) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lithodid crabs have rarely been observed over featureless bathyal sediment habitats on the continental slope near Monterey Bay (Jacobsen Stout et al., ; Taylor et al., ). Neolithodes diomedeae is known to occur in the Pacific Ocean from Central California to as far south as Chile, and South Georgia Island in the South Atlantic (Drumm et al., ). In the Monterey region, individuals have been observed from ~1225–1575 m depth (Jacobsen Stout et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Lithodid crabs have rarely been observed over featureless bathyal sediment habitats on the continental slope near Monterey Bay (Jacobsen Stout et al., ; Taylor et al., ). Neolithodes diomedeae is known to occur in the Pacific Ocean from Central California to as far south as Chile, and South Georgia Island in the South Atlantic (Drumm et al., ). In the Monterey region, individuals have been observed from ~1225–1575 m depth (Jacobsen Stout et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The NMFS Alaska Fisheries Science Center (AFSC) conducts surveys on the continental shelf and upper slope to a bottom depth of 1000 m in the Gulf of Alaska (von Szalay et al, 2010). Recent efforts by NMFS to document the diversity of Alaska's marine invertebrate fauna (Drumm et al, 2013;Drumm et al, in press) have revealed new records for species in the area. A standard practice for AFSC surveys is the collection and identification of fish stomach contents to understand the food habits of commercial fishes.…”
Section: Introductionmentioning
confidence: 99%